The Impact of Medical Insurance on Household Stock Market Participation: Evidence From China Household Finance Survey - Shi, Gui Fen; Li, Mei; Shen, Tao-Tao; Ma, Yue (Frontiers in Public Health, 2021)
This paper explores the impact of medical insurance on the possibility of household participation in the stock market and the portfolio share of equity, applying Probit, and Tobit models with the data from China Household Finance Survey (CHFS). The empirical results highlight that participating in medical insurance can significantly increase the possibility of households participating in the stock market and the portfolio share of equity, and have passed the robustness tests, including propensity score matching (PSM), altering estimation methods, replacing explained variables, and eliminating samples. Besides, heterogeneity analysis shows that the impact of medical insurance on household stock market participation is more significant in eastern region, urban areas, and households with higher income level. Further mechanism analysis implies that household participation in medical insurance mainly affects their stock market participation through preventive savings effect. It is necessary to improve the medical insurance system and encourage household participation in stock market so as to further promote financial development in China.